The Role Of Digital Media In Maintaining Pakualaman Culture: Documentation And Community Engagement - Anggun Anindya Sekarningrum; Raden Arditya Mutwara Lokita (INJECT (Interdisciplinary Journal of Communication), 2024)
This research discusses the role of digital media in maintaining Pakualaman culture, particularly through social media. The main objective is to identify utilisation of digital media to document and engage the public in the preservation of Pakualaman culture. The official social media accounts of Pakualaman, including Instagram and YouTube, serve as channels for the dissemination of information regarding Pakualaman culture. Meanwhile, the public actively engages by sharing content on platforms such as Instagram, YouTube, and TikTok. This participation helps spread cultural values more widely. The diffusion of innovation theory is used to explain the adoption of digital technology by the public in preserving traditional culture. This research uses a descriptive qualitative method with interviews, observation, and digital content analysis as data collection techniques. The results of the study are expected to provide insight into the role of digital media in cultural preservation.